Analytical behavior of dodecagonal concrete-filled double skin tubular (CFDST) columns under axial compression. (November 2019) - Wang, Jun; Cheng, Xianfeng; Wu, Chao; Hou, Chuan-Chuan
ABSTRACT: Dodecagonal CFDST columns have been used in power transmission towers in China due to their lighter weight and lower manufacturing cost. In this paper, the axial compressive behavior of dodecagonal concrete-filled double skin tubular (CFDST) columns was investigated by finite element analysis. The different behaviors between dodecagonal CFDST columns and circular CFDST columns were compared through the load-deformation curves, contact pressure, longitudinal stress distributions in concrete and ultimate capacity. The developed finite element model was validated against experimental results in terms of load-displacement curves, failure modes, stress distributions and the ultimate strength of the tested specimens. Then a parametric analysis was performed by the verified finite element model on parameters including slenderness ratio, hollow ratio and diameter of the outer steel tubes. Research results showed that the confinement effects and the ultimate strength of dodecagonal CFDST columns were relatively weaker than those of the corresponding circular CFDST columns. At last, a design equation for the compressive capacity of dodecagonal CFDST columns was derived, and accurate predictions were obtained compared with the experimental results. Highlights: The axial compressive behavior of dodecagonal concrete-filled double skin tubular columns was investigated by ABAQUS; Behaviors between dodecagonal and circular CFDST columns were compared through the developed finite element model; Parametric analysis was performed on parameters including slenderness ratio, hollow ratio and diameter of steel tubes; Design equation for the compressive capacity of dodecagonal CFDST columns was derived, and accurate results were obtained.